Smart arduino boat by using bluetooth module / Megat Ahmad Faiz Megat Khairuddin & Lukhman Nur Hakim Ahmad Ridzuan - Megat Khairuddin, Megat Ahmad Faiz; Lukhman Nur Hakim, Lukhman Nur Hakim (2015)
For some people, there are like to play with the remote control device. This day, there are a lot of remote control device that had been made such as car remote control, drone, helicopter, and boat remote control. They are like to play with it because they can reduce their stress when play with it. This project can be applied to who interested to play with remote control. It also can fulfill the leisure time to teenagers from being wasted. This project also can build easily by using arduino and it also cheaper among the other remote control device. It also is one way to save money because it only use the recycle waste. This project can reduce stress among students and make happier. Radio control ( often abbreviated to RIC or simply RC) is the use of radio signals to remote control a device. Radio control is used for control of model vehicles from a hand-held radio transmitter. Industrial military, and scientific research organizations make use of radio controlled vehicles as well. In this model, it show how to control two DC motor by using arduino and motor driver. This model is use with conversion of the electrical energy to mechanical energy. The DC motor that are being use are to make the boat to move forward, backward, right and left. The DC motor is control by using Bluetooth module. Bluetooth module can transmit the signal from the application from the phone. The DC motor will follow the instruction from the phone